(3bUjOI HGfJ SYGOs - (3GdeGRfj, CHh GdeVqQH, cYH Hf RgjQ Hf CHj Sdei, J(B26(3g`s
(3ChdgG (B:s
(3HGfJ SYGO abdHj Gdjhe eJHhd (B*** (3eJje EKQgG de jaO ecHhd , heG SYGO ZOGI GdHjf EP QMdhG (B*** (3EdG CZf ZVjV GdWQa ecMhds
(3BNQgG (B:s
(3ef SQg cQe GdMjGI adG jRGd (B*** (3aj eZjH ef UGdMj GdCfUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 226s
(3eYLe GdeDdajf(B: 2 / 669s
(3cTa GdXfhf(B: 2 / 1329s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs